Oral Supplementation of the Vitamin D Metabolite 25(OH)D3 Against Influenza Virus Infection in Mice - Hayashi, Hirotaka; Okamatsu, Masatoshi; Ogasawara, Honami; Tsugawa, Naoko; Isoda, Norikazu; Matsuno, Keita; Sakoda, Yoshihiro (Nutrients, 2020)
Vitamin D is a fat-soluble vitamin that is metabolized by the liver into 25-hydroxyvitamin D [25(OH)D] and then by the kidney into 1,25-dihydroxyvitamin D [1,25(OH)2D], which activates the vitamin D receptor expressed in various cells, including immune cells, for an overall immunostimulatory effect. Here, to investigate whether oral supplementation of 25-hydroxyvitamin D3 [25(OH)D3], a major form of vitamin D metabolite 25(OH)D, has a prophylactic effect on influenza A virus infection, mice were fed a diet containing a high dose of 25(OH)D3 and were challenged with the influenza virus. In the lungs of 25(OH)D3-fed mice, the viral titers were significantly lower than in the lungs of standardly fed mice. Additionally, the proinflammatory cytokines IL-5 and IFN-γ were significantly downregulated after viral infection in 25(OH)D3-fed mice, while anti-inflammatory cytokines were not significantly upregulated. These results indicate that 25(OH)D3 suppresses the production of inflammatory cytokines and reduces virus replication and clinical manifestations of influenza virus infection in a mouse model.